Control of autonomous vehicles in drifting and executing evasive maneuvers - Yunan, Emily Fatima (2018)
Professional rally drivers are well known for drifting their cars while taking corners to slide through the corner faster. When drifting, the vehicle is operating at its handling limits as its rear tires are saturated. When a tire saturates, a vehicle no longer responds the same way to the same set of control inputs. A typical driver may lack the skills to properly control a vehicle under tire saturation, but with the advancement of autonomous driving systems, the control task of stabilizing a drifting car can be delegated to an intelligent control algorithm, thus opening up new control possibilities in these operating regimes. In this project, an autonomous RC car is built and a three degrees of freedom bicycle model with brush tire model is used to simulate the vehicle kinematics and dynamics system that is tasked to perform autonomous drift cornering and execute evasive maneuvers. The iterative linear quadratic regulator (iLQR) is employed to control the car into steady-state drift cornering and stabilize it about the drift cornering equilibrium. The same controller is then applied to evasive maneuvers as a trajectory planner. The car is to navigate towards a goal while laterally moving obstacles are introduced in its path.